Implementing Digital Storytelling in Learning Speaking to EFL Secondary Students - Solihat, Siti; Nugraha, Sidik Indra; Ridwan, Iwan (British (Jurnal Bahasa dan Sastra Inggris), 2025)
This study aims to explore the learning medium of digital storytelling (DST) and its advantages and disadvantages as a way to facilitate the development of speaking skills among secondary students in an English as a Foreign Language (EFL) classroom. This research adopts a qualitative approach with case study design, using classroom observations and interviews to gather data from EFL students at a secondary school. The findings highlighted three main activities in the implementation of digital storytelling, which were opening, main, and closing activities. Another finding was digital storytelling's advantages and disadvantages. The advantages were that digital storytelling could foster students' creativity and students were motivated to learn speaking with digital storytelling. However, time consuming and technology distraction and dependency were the disadvantages. Although DS is a useful pedagogical tool for teaching EFL speaking, its successful application depends on careful planning, sufficient technology, and teacher preparation.